OPTIMALISASI PENENUN SONGKET OLEH ORGANISASI DEKRANASDA (Dewan Kerajinan Nasional Daerah) TAPANULI UTARA DI KECAMATAN TARUTUNG - Sibagariang, Febri Yanty; Malau, Waston (Institut Agama Islam Ngawi, 2024)
Abstract: Songket is a typical Toba Batak cloth made using traditional looms without the help of machines. Songket has an important meaning for the Batak Toba ethnic community, namely through the color patterns and shapes of songket used in traditional events or ceremonies such as weddings or births. The formulation of the research problem is what are the stages in weaving Tarutung songket? What are the benefits obtained by songket weavers in Tarutung District? The aim of this research is to find out the stages in weaving Tarutung songket and also to find out what benefits Tarutung songket weavers get. The method used in this research is qualitative with a descriptive approach. This research was conducted in Tarutung District, North Tapanuli Regency. Data collection techniques are through interviews and documentation. The results of this research show that there are benefits obtained by Tarutung songket weavers from Dekranasda North Tapanuli. The benefits in question are increasing songket production and improving the community's economy.Kata Kunci: Songket Weavers, Dekranasda, Tarutung